The Newest Sappho: P. Sapph. Obbink and P. GC inv. 105, Frs. 1-4 Studies in Archaic and Classical Greek Song, vol. 2 - Bierl, Anton; Lardinois, André (Mnemosyne, Supplements, 2016)
In The Newest Sappho Anton Bierl and André Lardinois have edited 21 papers of world-renowned Sappho scholars dealing with the new papyrus fragments of poems by Sappho that were published in 2014. Readership: All interested in Classics, Greek and Roman literature, archaic lyric, song and performance culture, and anyone concerned with papyrology, archaic Greek culture, history, society, and religion